Analisis Capaian Kesejahteraan Masyarakat Dikaitkan dengan Anggaran Belanja Pemerintah Menggunakan Analisis Regresi - Ana Uluwiyah (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2018)
Government budgets from year to year always increase. The budget allocation has been determined based on the Minister of Finance Regulation Number 101 / PMK.02 / 2011 concerning Budget Classification. Some budget allocations are realized in Subsidized Expenditures, Social Aid Expenditures, and Aid Expenditures. The amount of the budget varies every year, according to the government program being launched. However, based on several welfare indicators, an increase in government spending has not contributed significantly from year to year. This research was conducted with the aim of analyzing whether the amount of government spending is influenced by several components of the level of welfare. Research only uses a number of welfare indicators, namely indicators of health, education, poverty, inflation. The research method with a quantitative analysis approach, with simple linear regression analysis. Based on the results of the study it was found that it turned out that only a few welfare indicator variables had a strong relationship with government assistance spending. Educational indicator variables do not affect the amount of government assistance spending.